Development of Learning Tools with the Discovery Learning Model to Improve the Critical Thinking Ability of Mathematics - Putri, Anike; Roza, Yenita; Maimunah, Maimunah (Journal of Educational Sciences, 2020)
This research was motivated by the still limited learning of mathematics as a means of supporting learning in the 2013Curriculum. The purpose of this study was to produce some products in the form of learning devices (syllabus, RPP andLKPD) on the material for the flat side building of VIII Middle School with discovery learning models that meet valid, practical, and effective criteria for improving students mathematical critical thinking skills. Learning tools are developed using the 4-D model, which are define, design, develop and assess. The research instrument used was an instrument of validity in the form of a validation sheet to assess the feasibility of the syllabus, RPP and LKPD as well as a practical instrument in the form of a teacher observation sheet activity in applying the discovery learning model and student questionnaire responses to assess the practicality of LKPD. The results of the validation of the experts stated that the product developed reached a valid category with an average rating of 76.67% for syllabus, 76.67% for RPP and 88.04% for LKPD. Learning devices are considered very practical in small group trials with an average response of 96.44% students and large group trials from the observation sheet of teacher activity 93.71% and the average response of students87.77%. The learning tools have been proved to improvestudents mathematical critical thinking skills in terms of an average N-gain of 0.53 in the medium category.